Exploring the potential of blood and urine protein electrophoresis in predicting 1-year mortality in acute kidney injury. - Deniz Yilmaz; Ezgi Sahin; Gizem Batar; Koray Caglayan; Emine Gulturk; Sengul Aydin Yoldemir (PLoS ONE, 2025)
This retrospective cohort study aimed to assess the predictive value of protein fractions obtained from blood and urine protein electrophoresis, along with various clinical and laboratory parameters, for 1-year all-cause mortality in acute kidney injury (AKI) patients. Data were collected from hospitalized patients who had been diagnosed with AKI. Demographics, smoking status, blood and urine electrophoresis results, serum gamma globulin levels, monoclonal gammopathy status, immunofixation results, serum free kappa (κ) and lambda (λ), and urine κ and λ levels were measured in addition to routine biochemistry and complete blood counts. In addition, serum free κ-to-λ ratio and urine κ-to-λ ratio were calculated. The primary endpoint was 1-year all-cause mortality and its association with electrophoresis-obtained data. Among the 295 patients included in the analyses, 65 (22.03%) experienced mortality, with higher mean age (72.75 ± 13.51) compared to the survival group (62.58 ± 16.59) (p < 0.001). Sex distribution showed no significant difference between groups. No significant disparities were observed in electrophoresis parameters and other laboratory values. Multivariable logistic regression showed that high age (OR: 1.038, 95% CI: 1.016-1.062, p = 0.001) and low albumin (OR: 0.450, 95% CI: 0.263-0.770, p = 0.004) were independent predictors of mortality. We find that the evidence gathered in the present study is insufficient to recommend the use of blood and urine protein fractions for diagnostic or prognostic purposes in patients with AKI. Nonetheless, the current data showing some notable variations in urine κ and λ levels suggest that further studies are warranted to explore this relationship.